Aid and Dutch disease in the South Pacific - David Fielding (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The impact of aid inflows on relative prices and output is ambiguous. Aid inflows that increase domestic expenditure are likely to cause real exchange rate appreciation, ceteris paribus. However, if this expenditure raises the capital stock in the traded goods sector, then output in this sector might not contract, at least in the steady state. Moreover, if investment in the nontraded goods sector is relatively high and/or productive, then there is not necessarily any real exchange rate appreciation in the steady state. We use time-series data to examine the impact of aid inflows on output and real exchange rates in ten South Pacific island states, and find aid inflows to produce a variety of outcomes in economies of different kinds.
Keywords: F41; O56; 330; aid; Dutch disease; South Pacific; Entwicklungshilfe; Dutch Disease; Wirkungsanalyse; Südpazifischer Inselraum